Pairing Toroidal and Magnetic Dipole Resonances in Elliptic Dielectric Rod Metasurfaces for Reconfigurable Wavefront Manipulation in Reflection. Issue 22 (17th September 2018) - Tsilipakos, Odysseas; Tasolamprou, Anna C.; Koschny, Thomas; Kafesaki, Maria; Economou, Eleftherios N.; Soukoulis, Costas M.
Abstract: A novel approach for reconfigurable wavefront manipulation with gradient metasurfaces based on permittivity‐modulated elliptic dielectric rods is proposed. It is shown that the required 2π phase span in the local electromagnetic response of the metasurface can be achieved by pairing the lowest magnetic dipole Mie resonance with a toroidal dipole Mie resonance, instead of using the lowest two Mie resonances corresponding to fundamental electric and magnetic dipole resonances as customarily exercised. This approach allows for the precise matching of both the resonance frequencies and quality factors. Moreover, the accurate matching is preserved if the rod permittivity is varied, allowing for constructing reconfigurable gradient metasurfaces by locally modulating the permittivity in each rod. Highly efficient tunable beam steering and beam focusing with ultrashort focal lengths are numerically demonstrated, highlighting the advantage of the low‐profile metasurfaces over bulky conventional lenses. Notably, despite using a matched pair of Mie resonances, the presence of an electric polarizability background allows to perform the wavefront shaping operations in reflection, rather than transmission. This has the advantage that any control circuitry necessary in an experimental realization can be accommodated behind the metasurface without affecting the electromagnetic response. Abstract : A novel approach for reconfigurable wavefront manipulation with gradient metasurfaces based on permittivity‐modulated elliptic dielectric rods is demonstrated, by precisely matching in frequency and quality factor the magnetic dipole resonance with an unexplored toroidal dipole resonance. Although relying on matched resonances, the presence of an electric polarizability background allows to perform the wavefront shaping operations in reflection.